MECHANIZED SUGAR CANE PLANTING:: aspects of this process - Moretto, Gabriel Aparecido; Cavichioli, Fábio Alexandre (Revista Interface Tecnológica, 2022)
The sugar and ethanol sector has an important role in the Brazilian economy, as the country is the world's largest producer of sugarcane, and the expectation is that this market will continue to grow. For a long time, planting was carried out manually, however technological advances allowed this sector to also experience changes in this context. The plantation carried out with quality contributes significantly to the longevity of the cane field, good productivity and positive impacts on production costs. The mechanized planting process, due to its characteristics, tends to bring advantages in several aspects, in which productivity stands out. The objective of this study is to highlight the positive aspects of mechanized sugarcane planting in terms of production quality. The methodology used was a literature review with consultation of articles available online. The results found show that mechanized planting effectively contributes to the quality of productivity.
Keywords: Sugar and Alcohol Sector; Agribusiness; innovation